Trilliumosides K and L, two novel steroidal saponins from rhizomes of Trillium govanianum, as potent anti-cancer agents targeting apoptosis in the A-549 cancer cell line - Bashir Ahmad Lone; Bashir Ahmad Lone; Misbah Tabassum; Misbah Tabassum; Anil Bhushan; Anil Bhushan; Dixhya Rani; Dixhya Rani; Urvashi Dhiman; Urvashi Dhiman; Ajaz Ahmad; Hilal Ahmad Mir; et al. (Frontiers in Chemistry, 2023)
Two novel steroidal saponins, trilliumosides K (1) and L (2), were isolated from the rhizomes of Trillium govanianum led by bioactivity-guided phytochemical investigation along with seven known compounds: govanoside D (3), protodioscin (4), borassoside E (5), 20-hydroxyecdysone (6), 5,20-hydroxyecdysone (7), govanic acid (8), and diosgenin (9). The structure of novel compounds 1-2 was established using analysis of spectroscopic data including 1D and 2D nuclear magnetic resonance (NMR) and high resolution mass spectrometry (HR-ESI-MS) data. All isolated compounds were evaluated for in vitro cytotoxic activity against a panel of human cancer cell lines. Compound 1 showed significant cytotoxic activity against the A-549 (Lung) and SW-620 (Colon) cancer cell lines with IC50 values of 1.83 and 1.85 µM, respectively whereas the IC50 value of Compound 2 against the A-549 cell line was found to be 1.79 µM. Among the previously known compounds 3, 5, and 9, the cytotoxic IC50 values were found to be in the range of 5–10 µM. Comprehensive anti-cancer investigation revealed that Compound 2 inhibited in vitro migration and colony-forming capability in the A-549 cell line. Additionally, the mechanistic analysis of Compound 2 on the A-549 cell line indicated distinctive alterations in nuclear morphology, increased reactive oxygen species (ROS) production, and decreased levels of mitochondrial membrane potential (MMP). By upregulating the pro-apoptotic protein BAX and downregulating the anti-apoptotic protein BCL-2, the aforementioned actions eventually cause apoptosis, a crucial hallmark in cancer research, which activates Caspase-3. To the best of our knowledge, this study reports the first mechanistic anti-cancer evaluation of the compounds isolated from the rhizomes of T. govanianum with remarkable cytotoxic activity in the desired micromolar range.